CTIM-02. PHASE II STUDY OF IPILIMUMAB AND NIVOLUMAB IN LEPTOMENINGEAL CARCINOMATOSIS. (12th November 2021) - Strickland, Matthew; Lee, Eudocia Quant; Wang, Nancy; Cohen, Justine; Chukwueke, Ugonma; Forst, Deborah; Eichler, April; Overmoyer, Beth; Lin, Nancy; Chen, Wendy; Bardia, Aditya; Juric, Dejan; et al.
Abstract: Leptomeningeal disease (LMD) is an increasingly common complication from solid tumor malignancies with a poor prognosis and limited treatment options. We conducted a single arm Phase II study of combined ipilimumab and nivolumab in patients with LMD from solid tumor malignancies (NCT02939300). Patients received manufacturer-specific dosing regimens of combined ipilimumab and nivolumab based on primary-tumor histology until definitive progression or unacceptable toxicity. The primary end point was rate of overall survival at 3 months (OS3). A Simon two-stage design was used to compare a null hypothesis OS3 of 18% against an alternative of 44%. Eighteen patients with diverse primary tumor histologies were enrolled and all received at least one dose of combined ipilimumab and nivolumab. Median follow up based on patients still alive was 8.0 months (range: 0.5 to 15.9 months). The study met its primary endpoint as 8 of 18 (OS3 0.44; 90% CI: 0.24 to 0.66) patients were alive at three months after enrollment. One third of patients experienced one (or more) grade-3 or higher adverse events possibly related to treatment. Two patients discontinued protocol treatment due to unacceptable toxicity (hepatitis and colitis, respectively). The most frequent adverse events overall included fatigue (N=7), nausea (N=6), fever (N=6), anorexia (N=6) and rash (N=6). Combined ipilimumab and nivolumab has an acceptable safety profile and demonstrates promising activity in LMD patients; this therapeutic approach should be studied in larger, multicenter clinical trials to validate these results as well as better identify patients who will benefit.